Submandibular Gland Reduction in Aesthetic Surgery of the Neck. Issue 3 (September 2015) - Mendelson, Bryan C.; Tutino, Roberto
<x xml:space="preserve">Abstract</x> Background: The indications for reduction of excessive submandibular gland volume in aesthetic rejuvenation of the neck have been well described, as has the surgical anatomy and the surgical technique. Despite this, submandibular gland reduction does not appear to be widely adopted, nor have significant case series been reported in the literature. This review of a consecutive series of aesthetic submandibular gland reductions was undertaken to provide a perspective about its place in neck contouring. Methods: A retrospective chart review was conducted of all patients on whom the senior author (B.C.M.) had performed submandibular gland reduction for aesthetic reasons. Complications and reoperations were specifically analyzed. Results: Submandibular gland reduction was performed in 112 of 736 consecutive face lifts between 2002 and 2013, an incidence of 13 percent in primary face lifts and 25 percent in secondary face lifts. The median patient age was 57 years, and 87 percent were women. Major complications were those requiring early reoperation (1.8 percent) to manage significant hematomas; one was potentially fatal. Minor complications (10.8 percent) were managed nonoperatively. Submandibular sialocele (4.5 percent) and marginal mandibular branch neurapraxia (4.5 percent) were the most frequent, and all resolved fully by 3 months. Significantly, no patient reported a permanent dry mouth. Conclusions: The complication rate with submandibular gland reduction is comparable to that of a neck lift with platysma plication alone, with some additional specific risks: (1) catastrophic airway compression from bleeding deep in the neck, (2) significant increase of neurapraxias in secondary neck lifts, and (3) a moderate incidence of benign submandibular sialocele. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.